(untitled) (Itinera, 2024)
As suggested by Walter Benjamin in the famous essay on The Work of Art in the Age of its Technological Reproducibility[1], the emergence of new technologies such as photography and cinema brought about a rearticulation of the collective sensorium, implying a perceptive modification of the modes of fruition, introducing the spectator to new somaesthetic habits and practices. Today, the idea of an essential change in the way we perceive the world has become true in a way that largely exceeds Benjamin’s expectations. Digital technologies have become more than just mere instruments. Rather, they have either taken the form of three-dimensional computer-generated and responsive environments, in which users interact through their bodies (like virtual reality) or have been deeply integrated into perceptual milieu and into human’s bodily self, permeating and shaping his everyday experience (as AI and augmented or mixed reality). This issue aims to draw a provisional map of possible paths and work directions for digital aesthetics, without claiming to be exhaustive. Great support in this direction comes from the heritage of the lively discussions held during the Summer School on Lake Como, from 29 May to 1 June 2023, at the prestigious venue of the Alessandro Volta Foundation in Como, under the direction of Maddalena Mazzocut-Mis. This gathering an opportunity to outline research axes by offering an active space for discussion that generated possibilities for problematic focus for both faculty and Ph.D. students. The present issue thus welcomes some of those suggestions which have blossomed and borne new fruit over the past year. At the same time, the large number of submissions we received led us to select additional texts that contribute to outlining an issue focusing on three main axes: Digital, Extended Realities, Artificial Intelligence.